If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8x + 3) = 0 Reorder the terms: 4(3 + 8x) = 0 (3 * 4 + 8x * 4) = 0 (12 + 32x) = 0 Solving 12 + 32x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 32x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 32x = 0 + -12 32x = 0 + -12 Combine like terms: 0 + -12 = -12 32x = -12 Divide each side by '32'. x = -0.375 Simplifying x = -0.375
| (a+6)(a+9)= | | x+x=5 | | 2x-2(x+1)=3x | | 5x(2)+19x-4= | | 2x-29x+10=3x | | 7-8(x+1)= | | 3r+57= | | -4x+12= | | (x-2)(x-.6667)(3x)=0 | | 8x-4-6x=12-32 | | 3x+x=83.70 | | y=3x^3-6x^2-2x+4 | | .4x=-.17 | | 3xz+(5x+3z)(7x-2xz+y-4z)= | | (6x+3)(6x+3)= | | y(3)-14y(2)+48y= | | 8k-4k=16 | | x-44=41 | | 3a=33 | | 16d+3=8d+35 | | 64a-(23a-70)= | | 4(x-8)=-19.2 | | 7+3(4x-6)=7-5(2x+1) | | 28=6c-8 | | 3e-2=12.4 | | 8p=46.4 | | 8(x-4)=24 | | 3(a+2)=30 | | 9e-8=28 | | -3(4-5x)=-42 | | Log(x-1)=0 | | (x+8)+(x+15)=9x+40 |